A Case Report on Toxic Epidermal Necrolysis in an Adult Filipino Pregnant Patient - Mendoza , Manuel; Olivar-Floro, Nica Minerva (Philippine Journal of Allergy, Asthma and Immunology, 2024)
Toxic epidermal necrolysis (TEN) is a rare, life-threatening dermatologic emergency characterized by extensive epidermal detachment, blistering, and painful mucocutaneous erosions. It is often associated with complications such as electrolyte imbalance, infections, sepsis, and even death. TEN prevalence in the general population is estimated at 1-2/1,000,000 per year. In the pregnant population, TEN occurrence is even more uncommon, as limited studies have been reported. This case report adds to the existing literature on TEN in a pregnant patient in the local setting. The patient is a 26-year-old Gravida 3 Para 1 (1011) who presented at 12 weeks age of gestation with progressive vesiculobullous lesions and skin detachment after intake of omeprazole, hyoscine, and metoclopramide for abdominal pain. A skin biopsy confirmed the diagnosis of TEN. Systemic corticosteroid was initiated and was gradually tapered with complete resolution of symptoms. TEN in pregnancy may pose a potentially life-threatening risk for the mother and the fetus. In this case, the use of systemic steroids was noted to be beneficial in preventing the potential sequelae in TEN. Emphasis on pharmacovigilance in TEN, even in low-risk drugs, especially during pregnancy, is paramount.